TRANSFORMASI ADAPTASI BANGUNAN DI PERMUKIMAN INFORMAL TEPI SUNGAI KAHAYAN - Murti, Nindita Kresna; Suprapti, Atiek; Sardjono, Agung Budi (Jurnal Arsitektur ARCADE, 2020)
Abstract: Many informal settlements in Indonesia have been unable to survive, this is due to changes that occur in the neighborhood. This change resulted in the not surviving of informal settlements, but this did not affect the informal settlements in the city of Palangkaraya, settlements on the banks of the Kahayan river were even more developed, and began to develop towards the mainland.As climate change and the global environment increase, there is a tendency for people to conceptualize adaptation in residential buildings as a process of survival and how adaptation is practiced by people who face the negative impacts of climate change, for example in informal settlements on the Kahayan river bank, where residents adapt to building their homes to be able to withstand environmental changes. Where the neighborhood is located there are tides of the river, as well as other environmental factorsThis study is to find out how the Kahayan River settlement communities can survive, with changes that occur in the environment by analyzing using 6 strategies in building adaptation, namely: Adjustable, Versatile, Refitable, Convertible, Scalable, and Movable (Robert Schmid, 2009). Adaptation that occurs in these settlements, namely on building houses that follow climate change, times, and the environment.Keyword: Informal Settlements, Kahayan River Edge, Adaptation, Transformation.Abstrak: Permukiman Informal di Indonesia banyak yang sudah tidak dapat bertahan, hal ini di karenakan adanya perubahan yang terjadi di lingkungan permukiman tersebut. Perubahan ini berakibat tidak bertahannya permukiman informal, namun hal ini tidak mempengaruhi permukiman informal di Kota Palangkaraya, permukiman yang berada di tepi sungai kahayan ini malah semakin berkembang, dan mulai berkembang menuju ke daratan.Seiring dengan meningkatnya perubahan iklim dan lingkungan global, ada kecenderungan masyarakat untuk membuat konsep adaptasi pada bangunan rumah tinggal sebagai proses untuk bertahan dan bagaimana adaptasi dipraktikkan oleh orang-orang yang menghadapi dampak negatif perubahan iklim, sebagai contoh pada permukiman informal yang berada di tepi sungai Kahayan, di mana warga beradaptasi pada bangunan rumah mereka untuk dapat bertahan terhadap perubahan lingkungan. Di mana lingkungan permukiman ini terdapat pasang surut air sungai, serta faktor lingkungan lainnya.Penelitian ini untuk mengetahui cara masyarakat permukiman tepi Sungai Kahayan dapat bertahan, dengan perubahan yang terjadi di lingkungan dengan menganalisa menggunakan 6 strategi dalam adaptasi bangunan, yaitu: Adjustable, Versatile, Refitable, Convertible, Scalable, dan Movable (Robert Schmid, 2009). Adaptasi yang terjadi pada permukiman ini, yaitu pada bangunan rumah yang mengikuti perubahan iklim, jaman, dan lingkungan.Kata Kunci: Permukiman Informal, TepiÂ  Sungai Kahayan, Adaptasi, Transformasi.